057 Ceiling Effect of Clomiphene Citrate on Testosterone to Estradiol Ratio in Eugonadal Infertile Men. (1st May 2022) - Liao, Y.; Chang, H.
ABSTRACT: Introduction: Study has shown that the Testosterone to Estradiol ratio (T/E2 ratio) has more impact over semen quality and sexual desire than Testosterone does alone. Clomiphene Citrate is a Selective Estrogen Receptor Modulator that had long been used as an empirical option in the management of idiopathic oligozoospermia. Clomiphene may change the Hypothalamus-Pituitary-Gonad axis and result in the T/E2 ratio alteration. There were no reliable data about the T/E2 ratio change after Clomiphene use in eugonadism. Objective: The aim of this preliminary study was to determine whether clomiphene citrate has an effect on T/E2 ratio in infertile patient with eugonadism. Methods: This study included a total of 24 male patients who was diagnosed as idiopathic infertility with Eugonadism. They all take Clomiphene Citrate (25mg/day) as empirical treatment. Blood test including Testosterone, estradiol, prolactin, LH and FSH were done before and 4 weeks after Clomiphene use. Paired T test was used to evaluate the significance of the hormone level change. Results: For all the patients, the T/E2 ratio did not show significantly increase after Clomiphene use. In the subgroup analysis, if the T/E2 ratio less than 0.2, clomiphene can yield a significant increase of T/E2 ratio, not vice versa. Conclusions: In conclusion, Clomiphene citrate may significantly increase Testosterone to Estradiol Ratio in eugonadal men under the premise of its ceiling effect (T/E2 ratio <0.20), providing us a possible guidance to the use of Clomiphene in this group of patients. Disclosure: Work supported by industry: no.